Exploring the Impact of Social Media Green Marketing on Students’ Green Attitude and Behavior - Hidayat, Taufiq; Subahan, Ahmad; Ramadhani, Aulia (Universitas Islam Kadiri, 2026)
This study examines the influence of Social Media Green Marketing (SMGM) and Receptivity to Social Media Marketing (RSMM) on Green Attitude (GAT) and its implications for Voluntary Green Behavior (VGB) among university students in Sampit, Kotawaringin Timur, Central Kalimantan. Grounded in the Knowledge Attitude Behavior (KAB) Theory, this quantitative survey research involved 151 purposively sampled respondents. Data were analyzed using SPSS to test hypothesized relationships. Results indicate significant positive effects of SMGM and RSMM on GAT (H1 and H2 accepted), and GAT significantly predicts VGB (H3 accepted). GAT mediates the relationship between SMGM and GAT (H4 accepted) and between RSMM and GAT (H5 accepted). These findings highlight how students' receptivity to green social media messages enhances environmental attitudes and voluntary green actions. The study expands the KAB framework in a non-metropolitan context and offers practical insights for educational institutions to leverage social media in fostering sustainable youth behaviors.